Social security as an instrument for creating populist attitudes - Plecka, Danuta; Rutkowska, Patrycja (Political Preferences, 2016)
Societal security is undoubtedly an instrument for creating populist attitudes. This is related primarily to the quality of different democratic mechanisms and their representations affecting the political system. However, in the largest extent the merge of societal security and populism are triggered by the political elite, and the recipients of their communication - the citizens. It is related to the belief, which is increasingly affecting the public that ‘the elite should do what people order them to’ (Markowski 2004: 14). Undoubtedly, this situation creates series of consequences related primarily to the lack of political and economic civic competences. On the other hand, it may contribute to the growth of citizens' dissatisfaction with the government actions that results in the loss of the legitimacy. Key words: social security, populist attitudes, populism